Blue lights. Series 2 [videorecording (DVD)] - Lawn, Declan; Patterson, Adam (Writer); McCann, Martin, 1983-; Brooke, Sian; Devlin, Katherine; Braniff, Nathan (BBC, 2024)
In Belfast, three PSNI recruits fight gangs, undercover agents, and even their own force.